2022
DOI: 10.3390/jcdd9120425
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-Field Ablation Using a Novel Ablation-Mapping Integrated System for Pulmonary Vein Isolation—A Preliminary Animal Study

Abstract: Objective: The purpose of this study is to evaluate the preliminary safety and effect of a pulsed electric field (PEF) ablation system. Methods: The pulmonary veins (PVs) and superior vena cava (SVC) were isolated with the pulsed field ablation (PFA) system, which included a PEF generator and an electrode. The effects of PFA were investigated in six porcines using a novel circular catheter with combined functions (mapping/ablation) designed to work with a cardiac mapping system. The PEF generator delivered a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A limitation of prior esophageal assessments after cardiac PFA was the chronic nature of the assessments. 13 15 , 20 , 21 As we have demonstrated in this report, esophageal lesions may be missed unless looked for within the early postablation period (2 to 3 days). Longer survival periods, in our report revealed minimal to no evidence of esophageal effects, suggesting that acute PFA lesions heal without significant residual damage.…”
Section: Discussionmentioning
confidence: 73%
“…A limitation of prior esophageal assessments after cardiac PFA was the chronic nature of the assessments. 13 15 , 20 , 21 As we have demonstrated in this report, esophageal lesions may be missed unless looked for within the early postablation period (2 to 3 days). Longer survival periods, in our report revealed minimal to no evidence of esophageal effects, suggesting that acute PFA lesions heal without significant residual damage.…”
Section: Discussionmentioning
confidence: 73%
“…Of these in vivo studies, only the large animal studies were designed to recapitulate clinically relevant methodologies regarding atrial tachyarrhythmia catheter ablation techniques in the appropriate anatomic structures. Nine studies were identified, seven conducted in various swine models [44][45][46][47][48][49][50] and two conducted in canine models [51,52] . Study designs and sample sizes varied widely [Table 1], and study durations ranged from 3 days [47,52] to 3 months; however, no pulmonary vein stenosis was reported in any of these preclinical studies.…”
Section: Preclinical Pulmonary Vein Findings With Atrial Pfamentioning
confidence: 99%
“…3,8,9 Other approaches used to deliver supratherapeutic PFA to the oesophagus include ablation from within the aorta towards the oesophagus, or from within the cardiac chambers close to the oesophagus, but without deviation. [12][13][14] The published reports employing these assessments for PFA technologies all had a survival period of 14-30 days; none reported any oesophageal damage even on histology after PFA. 3,[8][9][10][11][12][13][14] Two additional preliminary reports using the deviation model described the presence of oesophageal lesions secondary to PFA exposure; however, they differ from the above reports in that the oesophagus was examined at the acute time point (short-term survival).…”
Section: Preclinical Datamentioning
confidence: 99%
“…[12][13][14] The published reports employing these assessments for PFA technologies all had a survival period of 14-30 days; none reported any oesophageal damage even on histology after PFA. 3,[8][9][10][11][12][13][14] Two additional preliminary reports using the deviation model described the presence of oesophageal lesions secondary to PFA exposure; however, they differ from the above reports in that the oesophagus was examined at the acute time point (short-term survival). 15,16 One of these reports examined the oesophagus at 2 hours and the other at 48 hours post-ablation.…”
Section: Preclinical Datamentioning
confidence: 99%